Legal Remedy Against Regress Rights for Endosans Who Make Non-Payment / Non-Acceptance Judging from the Use of Securities in KUHD - Syananda AL Rizky (LEGAL BRIEF, 2020)
Basically the provisions regarding the right of regressions are regulated in the Commerial law code. Regres right means the right to collect. Within the legal framework of money orders, Regres rights is right to collect from the debtor must regres because debtor interested in not being willing to accept or not pay the money order requested on the day of payment. This regression right is given to the notes holder because the money order has been rejected by the interested ( non-acceptability) or interested recipient of the money order payment on the day of payment(non payment). If a non-acceptance occurs,the holder has a regress right to the debtor must regres. As for the debtor meant in the right of regres are all people who have the obligation to guarantee payment of the relevant notes. The debtor must regress cn be a publisher or endosan or avalist. The regresion itself can be exercised if there is no acceptance (non-acceptability) and no payment (non payment). In the case of non-payment after acceptance, regress can be directly addressed to acceptor itself. The acceptor is bound to pay the note because he has put his signature on the note when accepting the note. As such it is a mandatory regres that must meet payment.